ANALISIS PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS IV SD INPRES 1 TIKONG KABUPATEN PULAU TALIABU - Nur Fajar; La Jusu; Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies for forming students' religious character and to examine the process of religious behavioral transformation among Grade IV students at SD Inpres 1 Tikong, Pulau Taliabu Regency, through Islamic Religious Education (PAI) learning. This research employed a qualitative approach with a case study design, involving 32 research subjects consisting of 31 Grade IV students and 1 PAI teacher. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña through stages of data condensation, data presentation, and conclusion drawing, with validity ensured through source and technique triangulation. The findings reveal that religious character formation was carried out through three integrated strategies, namely the comprehension strategy through consistent delivery of religious material, the habituation strategy through daily routines including prayer, congregational dzuhur prayer, and Ramadhan intensive Islamic study, and the exemplary strategy through the teacher's genuine behavior as a character model for students. The character transformation process occurred gradually across three phases: external direction, habitual transition, and value internalization, in which behavior that was initially extrinsically driven evolved into habits rooted in students' intrinsic awareness. These findings contribute to the achievement of SDGs Goal 4 on inclusive and quality education, Goal 10 on reducing inter-regional disparities, and Goal 16 on building just and character-driven societies.